"I Share to Help Them See": A Mixed-Method Analysis of Faculty Use of Self-Disclosure in Diversity Courses. - Holman, Elizabeth Grace; Paceley, Megan S.; Courts, C. L. Dominique (Journal of Social Work Education)
Social work education promotes a critical lens through which students engage with power systems. As educators, faculty often decide whether to share their own identities with students, yet we lack research on reasons faculty choose to share (or not share) their identities, and the ways in which privilege and marginalization affect that decision. Using a mixed-method approach, this study (N=84) addresses that gap. Quantitative analysis revealed that age was associated with intentionally sharing that identity; no other social identity was significantly related to disclosure practices. Qualitative analysis revealed the nuanced reasons that faculty elected to disclose or not disclose their identities. Discussion of these findings is situated in critical pedagogy, examining how faculty address power structures in the classroom.